Asymptotical expansions in the Kubilius theorem of large deviations - Skrabutėnas, Rimantas (Lietuvos matematikos rinkinys, 2005)
In the present paper, a local theorem of large deviations for arithmetic functions defined in Knopfmacher’s semigroup is obtained.